Study of Microstructure, Morphology and Functional Groups of Titanium Dioxide (Tio2) Impregnated With Copper (Cu) - Asmin, La Ode; Isa, La (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This research aims to determine the differences in the microstructure, morphology, and functional groups of TiO2 (P-25) after being impregnated with Cu. Cu-impregnated TiO2 samples are synthesized using the impregnation method with TiO2 (P-25) and copper sulfate as precursors. The microstructure and functional groups of TiO2 (P-25) and Cu-TiO2 were investigated using X-ray diffraction (XRD), scanning electron microscope-energy dispersive x-ray (SEM-EDX), and Fourier transform infrared (FTIR) analysis. The lattice parameters (a, b, and c) of the TiO2 sample were found to be a = b = 0.3778 nm, c = 0.9494 nm, and these values increased to a = b = 0.3779 nm, c = 0.9496 nm after the addition of Cu. The distance between the lattices of the TiO2 sample was measured at 0.3505 nm and increased to 0.3509 nm after Cu addition. The average crystallite size of the TiO2 sample was 33 nm, which increased to 43 nm after Cu impregnation. The strain value decreased from 2.76×10^(-3) to 1.82×10^(-3) after Cu addition. SEM results revealed that the morphology of the particles from the Cu-doped synthesis showed agglomeration. The success of Cu doping was confirmed by EDX mapping, which showed the presence of Ti, O, and Cu evenly distributed on the TiO2 surface. The FTIR spectrum indicated that TiO2 (P-25) and Cu-TiO2 particles had absorption peaks at similar wave numbers. However, in the absorption area of 1000 cm^-1 to 1250 cm^-1, new absorption bands affiliated with Cu-O bonds appeared in the Cu-TiO2 sample, resulting from TiO2 vibrations after Cu addition.